If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + -6 = 7f + 24 Reorder the terms: -6 + 2d = 7f + 24 Reorder the terms: -6 + 2d = 24 + 7f Solving -6 + 2d = 24 + 7f Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2d = 24 + 6 + 7f Combine like terms: -6 + 6 = 0 0 + 2d = 24 + 6 + 7f 2d = 24 + 6 + 7f Combine like terms: 24 + 6 = 30 2d = 30 + 7f Divide each side by '2'. d = 15 + 3.5f Simplifying d = 15 + 3.5f
| x^2-4x-656= | | 8.1x+1.25=-11.9+10.3 | | 9=8y-7y+3 | | 6x+x^2+8=0 | | (7y^2-7y-7)-(4y^2+2y+3)= | | 12+x-15=y+((x+12)-(x-15)) | | M+2m+3m=12 | | 2(t+1)= | | -17b-0.97=-14.88-19.8b-14.65 | | (w*98)=115(x) | | 7w+3d=-12 | | 5y-4y+2=-5 | | 10n+12-9-7n+4n=16+15 | | 11g+3-5g=39 | | 5(4c-1)-5=18c+8 | | 5y+4a=13 | | 20+14z=11z-20-8 | | -185=-32+17r | | 4s+1k=3r | | 13n=69 | | 11x+24=-2 | | 8z+7=-5z-57 | | 8-n=-4+2(4-n) | | 5.25q-2(3q+1.25)=q+1 | | 4s+k=3r | | 9.2s=12.8s-3.96 | | 3y^2=72 | | -20p=-15.58-11.8p | | (9x-5)-(6x-8)= | | 2m+2n+2m+4n+8= | | 7x-5(5x+4)=142 | | 28M+16=4(4M-23) |